The Impact of Tropical Cyclones in Premonsoonal Season on Local Convection over the Al-Hajar Mountains in Oman during 2007–2018 - Salma Al-Zadjali; Zamzam Al-Rawahi; Hamid Al-Brashdi (Advances in Meteorology)
The tropical cyclones (TCs) and convective storms have a significant impact on triggering widespread flooding in vulnerable areas. However, it is not clear whether the TCs stimulate the convective precipitation over the Al-Hajar Mountains in Oman or suppress it although it had been shown in many studies that TCs suppress the local convection development. This study aims to test the applicability of the hypothesis that the TCs suppress the convection over mountainous to the Al-Hajar Mountains. In order to test the hypothesis of tropical cyclones’ impact on local convection development over the Al-Hajar Mountains, this study considers three different cases during the premonsoon season between 2007 and 2018. The results revealed that weak local convection is reported over the Al-Hajar Mountains during the presence of the cyclones in the Arabian Sea and during the period of their direct impacts. The rainfall in these cases was mainly from stratiform clouds. Therefore, the impact of TCs on the convective suppression over the mountains is applicable to the Al-Hajar Mountains. This study will provide decision-makers and policy creators with knowledge as to whether the Al-Hajar Mountains are susceptible and vulnerable to the risk of torrential downpour, flash flooding, and thunderstorms as what is believed to be.